The crystal structure of defect KBB’O6 pyrochlores (B,B’: Nb,W,Sb,Te) revisited from neutron diffraction data - Mayer, Sergio Federico (2018)
Three defect pyrochlores KNbWO6·xH2O, KNbTeO6 and KSbWO6 were synthesized by solid state reaction at 750 °C, from stoichiometric mixtures of K2C2O4, Sb2O3, Nb2O5, WO3 and 20% excess TeO2. A neutron powder diffraction (NPD) data analysis allowed unveiling some structural features. They are all defined in the cubic (Formula Presented) space group symmetry, with α = 10.5068(1) Å, 10.2466(1) Å and 10.2377(1) Å, respectively. Difference Fourier synthesis for KNbWO6·xH2O clearly showed the presence of crystallization water, with extra O’ oxygen and H+ atoms that were located from NPD data. These O’ oxygen atoms are placed at 32e Wyckoff sites, conforming a K2O’ sublattice interpenetrated with the covalent framework constituted by (Nb,W)O6 octahedra. The H+ ions coordinate the O’ atoms at partially occupied 96g Wyckoff sites while K+ ions shift also along 32e sites, but closer to the 16c special site (0,0,0). By contrast, extra H2O molecules are absent in the other two pyrochlores: in KNbTeO6 and KSbWO6 K+ ions are shifted along 32e (x,x,x) sites further away from the origin than for the previous material, and the higher covalency of the octahedral network determines more compact structures, with shorter B-O distances and narrower B-O-B angles in the proposed AB2O6 defect pyrochlore structure.